Meningkatkan Kemampuan Anak Usia 5-6 Tahun dalam Mengenal Huruf Hijaiyah melalui Media Flash Card - Aulia Fitriani Munthe; Nurlaili, Nurlaili (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to improve the ability to recognize hijaiyah letters in children aged 5-6 years through the use of flash cards at RA Aisyaturridho Aek, Batu City. The background of this study is the low ability of children to recognize, name, show, and differentiate hijaiyah letters due to the use of conventional learning methods and the lack of interesting and interactive learning media. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, where each cycle consisted of the planning stage, action implementation, observation, and reflection. The research subjects were 20 children in group B. Data collection techniques were carried out through observation and documentation, while data analysis used quantitative descriptive techniques by calculating the percentage of children's ability development. The results showed a gradual increase in the ability to recognize hijaiyah letters in each cycle. In the pre-cycle stage, the percentage of children's abilities reached 36.50%, then increased in cycle I to 52.40%, and in cycle II increased to 81.00% so that it has met the research success indicators. This increase shows that the use of flash cards is effective in helping children recognize hijaiyah letters through interesting visual stimulation and interactive learning activities. Thus, flash card media can be used as an alternative effective learning media to improve the ability to recognize hijaiyah letters in early childhood.